THE EFFECTIVENESS OF MY POCKETBOOK TO IMPROVING WRITING SKILLS OF INTEGRATED ISLAMIC ELEMENTARY SCHOOLS CHILDREN IN YOGYAKARTA - Albi Anggito; Hana Ika Safitri; Harun Harun; Ali Mustadi (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This research is based on the problem of students' writing skills in elementary schools which are still very low. This research aims to determine the effectiveness of